CARIES IN SCHOOL CHILDREN AND TREATMENT PREVENTIVE MEASURES - Sadriyev Nizom Najmiddinovich; Boboqulov Utkir Abdullo ugli; Eshonqulov Mirvohid Murod ugli; Xamroqulova Nasiba Ravshan qizi; Maxmatmurodov Shoxzod Alisher ugli (American Journals, 2023)
The prevalence and intensity of dental caries in children has decreased in many countries of the world over the past 20-30 years [1], and this phenomenon in the late XX and early XXI centuries coincided with the widespread introduction of systemic fluoridation programs.